DEVELOPMENT OF A HARD STALKED FRUIT PICKER USING MINI DC ACTUATOR - Tasliman Tasliman; Rino Wahyu Priambudi (UPT Penerbitan Universitas Jember, 2022)
Most of the fruit pickers still use a simple way to release the fruit from the stem, namely using a hook or pole. Picking in this way takes a long time, because often releasing the fruit with the end of the hook needs to be done several times until the fruit falls. In the type of fruit with hard stalks, the method that can be used to pick the fruit without any damage is by cutting. To do the picking on the fruit with small twigs, it is necessary to use a cutting method that does not cause swings. The most suitable picking mechanism for such conditions is shearing. The right time for harvesting usually lasts only a short time. If the fruit is not harvested in time, the quality will decline rapidly. The purpose of this research is to design a fruit picker with a cutting knife that is driven by a motor using a 12 Volt battery. From several choices of cutting methods, the selected cutting mechanism is by shearing. To obtain the shearing movement, the actuator part of the automatic car door lock is used. The voltage source is a 12 V battery. In functional testing the tool has been able to function as expected. In the performance test, a very good cutting speed was obtained, which was 0.12 seconds per cutting. The tool is also able to cut the stalks of kenitu, oranges and mangoes satisfactorily. In addition, the battery capacity is able to cut up to 2000 more stalks on a single charge. However, the actual picking test shows that the transfer efficiency from fruit to fruit is very low. Keywords: fruit, fruit picker, hard stalked fruit